Response to Gaseous NO2 Air Pollutant of P. fluorescens Airborne Strain MFAF76a and Clinical Strain MFN1032 - Kondakova, Tatiana; Catovic, Chloé; Barreau, Magalie; Nusser, Michael; Brenner-Weiss, Gerald; Chevalier, Sylvie; Dionnet, Frédéric; Orange, Nicole; Poc, Cécile Duclairoir (Frontiers in Microbiology, 2016)
Human exposure to nitrogen dioxide (NO2), an air pollutant of increasing interest in biology, results in several toxic effects to human health and also to the air microbiota. The aim of this study was to investigate the bacterial response to gaseous NO2. Two Pseudomonas fluorescens strains, namely the airborne strain MFAF76a and the clinical strain MFN1032 were exposed to 0.1, 5, or 45 ppm concentrations of NO2, and their effects on bacteria were evaluated in terms of motility, biofilm formation, antibiotic resistance, as well as expression of several chosen target genes. While 0.1 and 5 ppm of NO2did not lead to any detectable modification in the studied phenotypes of the two bacteria, several alterations were observed when the bacteria were exposed to 45 ppm of gaseous NO2. We thus chose to focus on this high concentration. NO2-exposed P. fluorescens strains showed reduced swimming motility, and decreased swarming in case of the strain MFN1032. Biofilm formed by NO2-treated airborne strain MFAF76a showed increased maximum thickness compared to non-treated cells, while NO2 had no apparent effect on the clinical MFN1032 biofilm structure. It is well known that biofilm and motility are inversely regulated by intracellular c-di-GMP level. The c-di-GMP level was however not affected in response to NO2 treatment. Finally, NO2-exposed P. fluorescens strains were found to be more resistant to ciprofloxacin and chloramphenicol. Accordingly, the resistance nodulation cell division (RND) MexEF-OprN efflux pump encoding genes were highly upregulated in the two P. fluorescens strains. Noticeably, similar phenotypes had been previously observed following a NO treatment. Interestingly, an hmp-homolog gene in P. fluorescens strains MFAF76a and MFN1032 encodes a NO dioxygenase that is involved in NO detoxification into nitrites. Its expression was upregulated in response to NO2, suggesting a possible common pathway between NO and NO2 detoxification. Taken together, our study provides evidences for the bacterial response to NO2 toxicity.